Development of Indonesian historical heritage comics to enhance elementary school students’ higher-order thinking skills - Yulina Ismiyanti; Yunita Sari; Jupriyanto Jupriyanto; Lolita Enfesta (Jurnal Prima Edukasia, 2026)
This study aimed to develop a digital comic based on Indonesian historical heritage and to examine its feasibility, practicality, and effectiveness in enhancing elementary school students’ higher-order thinking skills (HOTS). The research employed a Research and Development (R&D) approach using the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The participants involved 35 fifth-grade elementary school students selected through purposive sampling. Data were collected through expert validation sheets, teacher and student response questionnaires, and HOTS tests administered through pretests and posttests. The data were analysed using descriptive percentage analysis and paired sample t-tests. The results showed that the developed digital comic was categorized as very feasible based on expert validation, very practical based on teacher and student responses, and effective in significantly improving students’ HOTS as indicated by the statistical difference between pretest and posttest scores. These findings suggested that digital comics integrating Indonesian historical heritage could serve as an innovative and engaging instructional medium for promoting higher-order thinking in elementary social studies learning. The study implied that culturally contextual digital learning media could support HOTS-oriented instruction and contribute to the development of more meaningful and interactive learning environments in elementary education.